Literature Review Overview of Reproductive Health Knowledge Among Adolescent Social Media Users - Purwati, Ayu Endang; Asmarani, Sri Utami; Dewi, Sri Wulan Ratna (Yayasan Inspirasi El Burhani, 2024)
Introduction: Reproductive health is a state of health that includes a person's reproductive functions, systems and processes. It includes not only the absence of disease but also socio-cultural and mental health. Reproductive health in adolescents is receiving significant attention from the government because adolescence is a transitional period from childhood to adulthood that has its uniqueness and experiences the development of physical, mental, social and emotional maturity. Gadgets are used by all groups, especially adolescents. Adolescents spend time using gadgets every day, even in the learning process at school, making gadgets the most popular communication tool. The ease with which adolescents can access information through social media helps them to increase their knowledge in order to maintain their health, especially their reproductive health. Objective: To examine the picture of reproductive health knowledge among adolescent social media users. Method: The literature review was chosen as the method used to collect literature from the Google Scholar database for the publication year 2019 to 2023. The literature selected was full-text journals in the Indonesian language, and the reviewer got 5 articles that were by the objectives. Result: The results of the review obtained 8 articles that are by the theme of reproductive health knowledge in adolescent social media users. Conclusion: Social media influences adolescent knowledge about reproductive health, but does not determine high or low knowledge.